Parameters of fermentation and rumen microbiota of Nellore steers fed with different proportions of concentrate in fresh sugarcane containing diets - Ribeiro Junior, Carlos S. [UNESP]; Messana, Juliana D. [UNESP]; Granja-Salcedo, Yury T. [UNESP]; Canesin, Roberta C.; Fiorentini, Giovani [UNESP]; San Vito, Elias [UNESP]; Furlan, Luiz R. [UNESP]; Reis, Ricardo A. [UNESP]; Berchielli, Telma T. [UNESP] (Taylor & Francis Ltd, 2016)
The objective of this study was to evaluate the effect of a fresh sugarcane-based diet and different roughage-to-concentrate ratios (70: 30, 60: 40, 40: 60 and 20: 80) on the rumen microbiota associated with rumen fermentation parameters and the intake and apparent digestibility of nutrients in Nellore steers. Eight rumen-cannulated Nellore steers (331 +/- 8 kg BW) were distributed in a double 4 x 4 Latin square design balanced for the control of the residual effect. The ruminal pH decreased (p < 0.01) and the concentrations of N-NH3, isovaleric and valeric acids increased linearly (p < 0.05) with an increase dietary concentrate level. Furthermore, an increased concentrate proportion reduced the population of Fibrobacter succinogenes and Ruminococus flavefaciens (p < 0.01) and increased the population of Selenomonas ruminantium and Megasphaera elsdenii (p < 0.01). The protozoa count revealed a predominance of the genus Entodinium. The synthesis of microbial N [g/d] and the efficiency of microbial synthesis [g of microbial N/kg of organic matter apparently digested in the rumen] increased as the proportion of concentrate was increased (p < 0.05). Therefore, it can be concluded that an increasing proportion of concentrate in sugarcane-containing diets enhances the synthesis of microbial protein and does not alter the fibre digestibility, although the population of fibre fermenting bacteria was reduced.
Keywords: Bacteria; digestibility; microbial protein; protozoa; rumen fermentation; steers; sugarcane